Corrosion Behavior and Passive Film Composition of Alloy 825 in High Temperature and High H2S-CO2 Containing Environment - Feng, Zhe; Fan, Xuehua; Wang, Zhu; Yu, Yong; Chen, Lijuan; Du, Yanxia; Dong, Lei (Frontiers in Materials, 2021)
The effect of high temperature on corrosion behavior and passive film composition of Ni-based alloy 825 in H2S-containing environment was investigated by Confocal Laser Microscope (CLM), Scanning Electron Microscope (SEM), Energy Dispersive Spectrometer (EDS), and X-ray Photoelectron Spectroscopy (XPS). The experiment was carried out at 150 and 230°C in NaCl solution. The partial pressure of H2S was set to 1.2 MPa and CO2 was set to 3.2 MPa. The results showed that Ni-based alloy 825 presented good general corrosion resistance. Pitting corrosion was likely to occur at 230°C because of Cr depleted in the passive film. NiS appeared at high temperature and is damaging to protectiveness of passive film.